C‐Reactive Protein, Vitamin D Deficiency, and Slow Gait Speed. Issue 9 (8th August 2013) - Kositsawat, Jatupol; Barry, Lisa C.; Kuchel, George A.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the independent and joint effects of C‐reactive protein (CRP) and 25‐OH vitamin D (25(OH)D) levels on mobility disability in older persons. Design U.S. population‐based cross‐sectional study. Setting National Health and Nutrition Examination Surveys (2001–2002). Participants Individuals aged 50 and older (N = 1, 826). Measurements C‐reactive protein (mg/dL), with high CRP defined as ≥0.2 mg/dL, and 25(OH)D levels (ng/mL) operationalized as severe deficiency (<10 ng/mL), deficiency (10–19.9 ng/mL), insufficiency (20–29.9 ng/mL), and normal (≥30 ng/mL). Mobility disability was operationalized as gait speed of <0.8 m/s while completing a 20‐foot walk (6.1 m). Results High CRP and low 25(OH)D levels were associated with slow gait speed. Individuals with high CRP levels and severe vitamin D deficiency were more likely to have slow gait speed than were those with neither risk factor (odds ratio = 3.54, 95% confidence interval = 1.42–8.84, P = .007). A significant positive association between vitamin D level and gait speed was found only in those with high CRP in stratified analyses. Whites and blacks showed similar findings as the overall population. Conclusion These findings provide evidence of a potential joint effect of vitamin D and CRP on gait speed, suggesting that evaluation and correction of vitamin D levels may be especially important in individuals with high CRP levels.